Magnetic susceptibility components reveal different aspects of neurodegeneration in alpha-synucleinopathies - Oliver C. Kiersnowski; Pietro Mattioli; Lucia Argenti; Laura Avanzino; Francesco Calizzano; Andrea Diociasi; Laura Falcitano; Chunlei Liu; Mattia Losa; Federico Massa; Silvia Morbelli; Beatrice Orso; et al. (Scientific Reports)
Abstract Nigrostriatal dopaminergic degeneration in alpha-synucleinopathies is indirectly reflected by low dopamine transporter (DaT) uptake through [123I]FP-CIT-SPECT. Bulk magnetic susceptibility ( $$χ$$ ) in the substantia nigra, from MRI-based quantitative susceptibility mapping (QSM), is a potential biomarker of nigrostriatal degeneration, however, QSM cannot disentangle paramagnetic (e.g. iron) and diamagnetic (e.g. myelin) sources. Using the susceptibility source-separation technique DECOMPOSE, paramagnetic component susceptibility (PCS) and diamagnetic component susceptibility (DCS) were studied in prodromal and overt alpha-synucleinopathies, and their relationships with DaT-SPECT specific binding ratio (SBR) and clinical scores. 78 participants were included (23 controls, 30 prodromal and 25 overt alpha-synucleinopathies). Prodromal patients were subdivided into groups with positive or negative DaT-SPECT (SBR Z-scores below or above -1, respectively). Correlations of putamen and caudate SBR Z-scores with PCS and DCS in the substantia nigra, putamen, and caudate were investigated. Increased PCS was observed in the substantia nigra of prodromal alpha-synucleinopathy patients with positive DaT-SPECT compared to controls and prodromal patients with negative DaT-SPECT. SBR Z-scores in the putamen correlated with increased PCS in the substantia nigra and reduced |DCS| in the putamen, which may reflect dopaminergic degeneration ascribable to iron accumulation and nigrostriatal neuron axonal loss, respectively.